Problemas de salud mental y percepción de salud mental en estudiantes de enfermería durante la pandemia COVID-19 Iquitos 2021 - Curichimba Davila, Prisila Martina (2023)
The objective of this research study was to determine the relationship between mental health problems (depression, anxiety, stress) and the perception of mental health in students of the nursing school of the UNAP during the Covid-19 pandemic, Iquitos 2021. The type of study was quantitative, descriptive, correlational, non-experimental, cross-sectional design, the population consisted of 452 students of the nursing faculty and the sample consisted of 208 students; the technique used for data collection was the self-administered survey. The results obtained show that there is a statistically significant relationship between mild depression and the perception of moderate mental health, obtaining a Chi of 39.046, and a p=0.000; < 0.05; there is a statistically significant relationship between mild anxiety and the perception of moderate mental health, obtaining a Chi of 31.099, and a p=0.000; < 0.05; there is a statistically significant relationship between mild stress and the perception of moderate mental health, obtaining a Chi of 28.549, and a p=0.000; < 0.05; concluding that the students who presented greater mental health problems, had a lower perception of their mental health and vice versa, which indicates that it is necessary to protect their mental health through activities of promotion and prevention of mental health in the institution.